The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1097/00001888-200012000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Comprehensive Relative-value—Based Incentive Plan in an Academic Family Medicine Department

Abstract: The authors describe the implementation and first three years (1997-1999) of a department-wide incentive plan of the Department of Family Medicine at the State University of New York at Buffalo School of Medicine and Biomedical Sciences. By using a consensus approach, a representative elected committee designed a clinical relative value unit (explained in detail) that could be translated to equally value and reward faculty efforts in patient care, education, and research and which allowed the department to avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 14 publications
2
64
0
1
Order By: Relevance
“…Six studies explicitly reported a retrospective approach to data collection. 3,6,7,10,11,13 The authors of the two remaining studies confirmed that data collection was prospective. 8,9 None of the studies included an active comparator.…”
Section: Features Of the Studiesmentioning
confidence: 80%
See 2 more Smart Citations
“…Six studies explicitly reported a retrospective approach to data collection. 3,6,7,10,11,13 The authors of the two remaining studies confirmed that data collection was prospective. 8,9 None of the studies included an active comparator.…”
Section: Features Of the Studiesmentioning
confidence: 80%
“…3,6,11 The need for staff support for managing productivity assessment was reported for four strategies. 3,6,8,11 Four strategies were described as offering either web-based access 9,11 or regular feedback to faculty.…”
Section: Features Of the Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A few have reported their experience in clinical departments, though none has included a pathology department (7,11,(17)(18)(19). In this report, we describe the UCDavis Department of mission-based reporting system.…”
Section: Introductionmentioning
confidence: 99%
“…A few centers have developed incentive-based faculty compensation programs, but the productivity measures and compensation levels of these programs have been based on internally devised scales. 2,3 It is difficult to assess the success of these programs without a comparison to national productivity standards.…”
mentioning
confidence: 99%